Beneficial Effect of Short-Term Supplementation of High Dose of Vitamin D3 in Hospitalized Patients With COVID-19: A Multicenter, Single-Blinded, Prospective Randomized Pilot Clinical Trial - Cervero, Miguel; López-Wolf, Daniel; Casado, Guiomar; Novella-Mena, Maria; Ryan-Murua, Pablo; Taboada-Martínez, María Luisa; Rodríguez-Mora, Sara; Vigón, Lorena; Coiras, Mayte; Torres, Montserrat (Frontiers in Pharmacology, 2022)
There is now sufficient evidence to support that vitamin D deficiency may predispose to SARS-CoV-2 infection and increase COVID-19 severity and mortality. It has been suggested that vitamin D3 supplementation may be used prophylactically as an affordable and safe strategy that could be added to the existing COVID-19 standard treatment. This multicenter, single-blinded, prospective randomized pilot clinical trial aimed to evaluate the safety, tolerability, and effectiveness of 10,000 IU/day in comparison with 2,000 IU/day of cholecalciferol supplementation for 14 days to reduce the duration and severity of COVID-19 in 85 hospitalized individuals. The median age of the participants was 65 years (Interquartile range (IQR): 53-74), most of them (71%) were men and the mean baseline of 25-hydroxyvitamin D (25(OH)D) in serum was 15 ng/mL (standard deviation (SD):6). After 14 days of supplementation, serum 25(OH)D levels were significantly increased in the group who received 10,000IU/day (p<0.0001) (n=44) in comparison with the 2,000IU/day group (n=41), especially in overweight and obese participants, and the higher dose was well tolerated. A fraction of the individuals in our cohort (10/85) developed acute respiratory distress syndrome (ARDS). The median length of hospital stay in these patients with ARDS was significantly different in the participants assigned to the 10,000IU/day group (n=4; 7 days; IQR: 4-13) and the 2,000IU/day group (n=6; 27 days; IQR: 12-45) (p=0.04). Moreover, the inspired oxygen fraction was reduced 7.6-fold in the high dose group (p=0.049). In terms of blood parameters, we did not identify overall significant improvements, although the platelet count showed a modest but significant difference in those patients who were supplemented with the higher dose (p=0.0492). In conclusion, the administration of 10,000IU/day of vitamin D3 for 14 days in association with the standard clinical care during hospitalization for COVID-19 was safe, tolerable, and beneficial, thereby helping to improve the prognosis during the recovery process.